Early Religious Practice in Norse Greenland: From the Period of Settlement to the 12th Century - Umbrich, Andrew, 1988- (2012)
Norse Greenland is presented in the sagas as being settled by Pagans. The archaeological record states that only Christians ever inhabited Greenland. This thesis explores the clashing views of the written and archaeological record in order to come to a suitable conclusion on the following question: Where the Greenland Norse pagans, Christians, or both at the time of settlement?